Activation of pig oocytes using nitric oxide donors - Petr, Jaroslav; Rajmon, Radko; Rozinek, Jirí; Sedmíková, Markéta; Jeseta, Michal; Chmelíková, Eva; Svestková, Dana; Jílek, Frantisek (Molecular reproduction and development, 2005)
Nitric oxide (NO) plays an important role in intracellular signaling, but its role during the activation of mammalian oocytes is little understood. In our study, in vitro matured pig oocytes were cultured with NO-donors-S-nitroso-N-acetylpenicillamine (SNAP) or sodium nitropruside (SNP). These treatments were able to induce parthenogenetic activation of pig oocytes matured in vitro. The specificity of this effect was confirmed by the activation of oocytes by exogenous endothelial nitric oxide synthase (eNOS) microinjected in the oocyte with its activator calmodulin. Relatively long exposure (10 hr) is needed for activation of pig oocytes with 2.0 mM SNAP. An active NOS is necessary for the NO-dependent activation of pig oocytes because NOS inhibitors L-NMMA or L-NAME are able to inhibit activation of oocytes with NO-donor SNAP. On the basis of our data, we conclude that the NO-dependent activating stimulus seems inadequate because it did not induce the exocytosis of cortical granules. Also, the cleavage of parthenogenetic embryos was very low, and embryos did not develop beyond the stage of eight blastomeres.
Keywords: kalmodulin; donory oxidu dusnatého; techniky in vitro; NG-Nitroarginine Methyl Ester; Female; oxid dusnatý; synthasa oxidu dusnatého; Calmodulin; zvířata; Nitric Oxide; nitroprusid; Cells, Cultured; Nitric Oxide Synthase; oocyty; Penicillamine; Swine; ženské pohlaví; kultivované buňky; penicilamin; In Vitro Techniques; synthasa oxidu dusnatého, typ III; inhibitory enzymů; NG-nitroargininmethylester; Animals; Nitric Oxide Donors; Oocytes; Nitric Oxide Synthase Type III; Nitroprusside; Enzyme Inhibitors; prasata